Examining Students’ Motivation to Continue Using AI-Chatbot for Academic Assignment - Ferdhy Ramadan; Puspita Kencana Sari; Yusza Reditya Murti (Jurnal Sistem Informasi, 2024)
This study focuses on the motivations of engaged Indonesian university students who frequently utilize the AI-chatbot to assist them with their academic work. This research modifies Post-Acceptance of Information System Continue model with the ECT (Expectation Confirmation Theory) and TAM (Technology Acceptance Model) to explore constructs to determine what motivates students to continue using the emerging AI-chatbot, namely BING. The findings revealed a positive and substantial correlation between Perceived Information Quality (PEIQ), Confirmation (CON), Perceived Usefulness (PEU), Perceived Enjoyment (PEE), Satisfaction (SAT), and Continue Intention (COI). Confirmation (CON) has a significant impact on how usefulness and enjoyment BING is perceived, which influences Satisfaction and the decision to continue using BING. Confirmation (CON) and Perceived Ease of Use (PEEOU) have no clear correlation with Satisfaction (SAT). Some contributions are discussed in this study, both theoretically and practically.